Social & Psychological Factors Associated with Oral Analgesic Use in Knee Osteoarthritis Management - Vina, E.R. (Osteoarthritis Cartilage, 2019)
OBJECTIVE: Determine modifiable social and psychological health factors that are associated with use of oral opioid and non-opioid medications for OA. METHODS: Patients were categorized based on use of the following oral medications: opioids (with/without other oral analgesic treatments), non-opioid analgesics, and no oral analgesic treatment. We used multinomial logistic regression models to estimate adjusted relative risk ratios (RRRs) of using an opioid or a non-opioid analgesic (vs. no oral analgesic treatment), comparing patients by levels of social support (Medical Outcomes Study scale), health literacy (“How confident are you filling out medical forms by yourself?”), and depressive symptoms (Patient Health Questionnaire-8). Models were adjusted for demographic and clinical characteristics. RESULTS: In this sample (mean age 64.2 years, 23.6% women), 30.6% (n=110) reported taking opioid analgesics for OA, 54.2% (n=195) reported non-opioid use, and 15.3% (n=55) reported no oral analgesic use. Opioid users had lower mean social support scores (10.0 vs. 10.5 vs. 11.9, p=0.007) and were more likely to have moderate-severe depressive symptoms (42.7% vs. 24.1% vs. 14.5%, p<0.001). Health literacy did not differ by treatment group type. Having moderate-severe depression was associated with higher risk of opioid analgesic use compared to no oral analgesic use (RRR 2.96, 95%CI 1.08–8.07) when adjusted for sociodemographic and clinical factors. Neither social support nor health literacy was associated with opioid or non-opioid oral analgesic use in fully adjusted models. CONCLUSIONS: Knee OA patients with more severe depression symptoms, compared to those without, were more likely to report using opioid analgesics for OA.